Effects of Neuropeptide Y on Stem Cells and Their Potential Applications in Disease Therapy - Song Peng; You-li Zhou; Zhi-yuan Song; Shu Lin (Stem Cells International)
Neuropeptide Y (NPY), a 36-amino acid peptide, is widely distributed in the central and peripheral nervous systems and other peripheral tissues. It takes part in regulating various biological processes including food intake, circadian rhythm, energy metabolism, and neuroendocrine secretion. Increasing evidence indicates that NPY exerts multiple regulatory effects on stem cells. As a kind of primitive and undifferentiated cells, stem cells have the therapeutic potential to replace damaged cells, secret paracrine molecules, promote angiogenesis, and modulate immunity. Stem cell-based therapy has been demonstrated effective and considered as one of the most promising treatments for specific diseases. However, several limitations still hamper its application, such as poor survival and low differentiation and integration rates of transplanted stem cells. The regulatory effects of NPY on stem cell survival, proliferation, and differentiation may be helpful to overcome these limitations and facilitate the application of stem cell-based therapy. In this review, we summarized the regulatory effects of NPY on stem cells and discussed their potential applications in disease therapy.